2003
DOI: 10.1002/jbm.a.10509
|View full text |Cite
|
Sign up to set email alerts
|

Pore size in implanted polypropylene filters is critical for tissue organization

Abstract: Widely different implant materials induce surprisingly similar tissue reactions in vivo in contrast to their in vitro responses. Increasing attention has recently been given to the surface texture of the material. When both the material composition and the surface topography are varied, the surface topography seems to be the predominant factor for the induced tissue response. The present study addresses differences in the tissue response to commercially available Millipore mesh filters of polypropylene with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The progressive development of an avascular fibrous capsule can compromise the long-term performance of a graft [19,20]. Maintaining high vascularity around the implant is thought to be a means of reducing fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…The progressive development of an avascular fibrous capsule can compromise the long-term performance of a graft [19,20]. Maintaining high vascularity around the implant is thought to be a means of reducing fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, another study reported that unique biological activity including enhanced angiogenesis has been noted for implanted porous materials with tightly controlled pore size distributions around 35 ÎŒm [55]. The cellular responses of angiogenesis, inflammation, foreign body capsule formation, and tissue infiltration in vivo have all shown some dependence on average pore size and pore size distribution, but the specific range is still not conclusive [56], [57].…”
Section: Pore Sizementioning
confidence: 92%
“…While we have focused on the in vitro effects of pore size on epithelial cells, recent publications have indicated that pore size contributes to the in vivo response. Angiogenesis, inflammation, foreign body capsule formation, and tissue invasion have all shown a dependence on pore size [31][32][33][34][35][36]. Interestingly, unique biological reactivity, including enhanced angiogenesis, has recently been noted for implanted porous materials with tightly controlled pore-size distributions around 35 mm [36].…”
Section: Article In Pressmentioning
confidence: 99%